Sources of growth and supply response: a cross-commodity analysis of China's grain sector - Colby, Hunter; Diao, Xinshen; Somwaru, Agapi (Ashgate, 2004)
The authors use a growth accounting method to assess the growth of the rice, wheat, corn, and soybean market in China between 1978 and 1997 and make projections on future trends based on current governmental policies. The authors estimate the supply response of the four grains using a multiproduct framework.